HUBUNGAN ANTARA PELAKSANAAN PEMBELAJARAN PRAKTIK DAN KESIAPAN KERJA DI SMKN2 WONOSARI - Ryan Dwi Rahmanto; Gunadi Gunadi (Universitas Negeri Yogyakarta, 2022)
AbstractTheiobjectives of thissstudy were (1) to determine the implementation of practical learning at SMK N 2 Wonosari, (2) to determineethe levellof work readiness ofsstudents at SMK N 2 Wonosari, and (3) to determine the relationshippbetween theeimplementation of practical learning and work readiness of class students. XII Automotive Engineering Skills Program at SMK N 2 Wonosari (TKRO). This type of research is descriptive statistics with a quantitative approach. This research includes population research, with a total of 91 students of class XII of the Automotive Engineering Expertise Program at SMK N 2 Wonosari. The research instrument is aaquestionnaire. The validityyof the instrumenttwas tested usinggthe product moment formula. Instrument reliability was calculated using the Cronbach Alpha formula. The data obtained were tested using descriptive statistics, correlation analysis with regression with the help of the SPSS version 23 computer program. The resultssshowed thatt: (1) the implementation of practical learningaat SMK N 2 Wonosari was included in the very high category with a scale of 1-4 obtained 3.53, (2) The level of work readiness of class XII students of the expertise program of the Automotive Engineering Expertise Program at SMK N 2 Wonosari is included in the high category with a scale of 1-4 obtained 3.39, (3) Thereeis a relationshippbetweennthe implementationoof practical learning and work readiness. This is evidenced by the significance value of 5% level 0.000 0.05. In the producttmoment correlation analysis, the correlationncoefficient (rxy) with N=91 is 0.684 at a 5% significance level of 0.207. The data shows that rcount is greater than rtable (0.6840.207).